Pendampingan Pembuatan dan Pemanfaatan Media Gambar Sebagai Bahan Ajar untuk Meningkatkan Keterampilan Membaca Bahasa Inggris Siswa - Umar Bakri; Ozi Satria; Rijnan (Pendidikan Al-Gafari, 2024)
Picture media is one of the effective teaching aids to stimulate children in learning, picture media is used as a means to achieve learning objectives. Picture media can facilitate understanding and strengthen memory, with picture media teachers can foster students' interest in reading. This community dedication aims to improve the English reading skills of 7th-grade students at SMP Islam Arrahmaniyah through mentoring in making and utilizing picture media as teaching materials. The methods used include training for teachers in designing creative and interesting picture media and direct mentoring in implementing it in the classroom. This activity is carried out in three stages, namely (1) socialization and training in making picture media, (2) mentoring in implementing picture media in learning, and (3) evaluation of learning outcomes. The activity results showed an increase in student enthusiasm and understanding of reading English texts, as well as an increase in teachers' ability to develop innovative teaching materials. Thus, this activity not only improves students' reading skills but also empowers teachers to create a more interactive and effective learning environment. It is hoped that this activity can be a model for other schools in improving the quality of English learning.